Critical insights into analytical methodologies for lidocaine hydrochloride and diltiazem hydrochloride: a comparative review - Shivani Patel; Archita Patel; Chandni Chandarana; Bhavesh Patel; Mehul Patel; Umang Shah; Swayamprakash Patel; Nilay Solanki; Drashti Shah; Ashish Patel (Future Journal of Pharmaceutical Sciences)
Abstract Background This study focuses on a fixed-dose combination of lidocaine hydrochloride and diltiazem hydrochloride for the treatment of anal fissures, where lidocaine acts as an anesthetic and diltiazem serves as a slow calcium channel blocker. The objective is to provide a concise overview of the fundamental principles of spectrophotometric and chromatographic methods for quantitative analysis from 2012 to 2022. Main text This review highlights the development of novel techniques for both individual and simultaneous quantification, including ultraviolet–visible spectrophotometry (UV–Vis), high-performance liquid chromatography, and high-performance thin-layer chromatography. Additionally, it addresses the capability of various analytical methods to detect and measure compounds at microgram to nanogram levels. Conclusions From 2012 to 2022, significant advancements in spectrophotometric and chromatographic methods for analyzing pharmaceutical compounds such as lidocaine and diltiazem have been made. These advancements have improved the sensitivity, accuracy, and efficiency of quantitative analyses, contributing to better quality control and therapeutic efficacy of pharmaceutical products. Modern techniques can detect and quantify compounds at microgram to nanogram levels, ensuring accurate dosing and safety assessments in pharmaceutical formulations.